The content of water-soluble phenolic compounds in the leaves of woody plants growing in the area of sanitary protection zones of enterprises of the industrial region of Zaporizhzhya - Sklyarenko, A.; Bessonova, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
The article presents the results of studying the accumulation of water-soluble phenolic compounds in the leaves of woody plants growing in the area of sanitary protection zones of a number of enterprises of Zaporizhzhya: Zaporizhzhya Titanium & Magnesium Combine, Zaporizhzhya Aluminium Plant, Zaporizhzhya Abrasive Plant, Zaporizhstal, Zaporizhcoke, Zaporizhzhya Ferroalloy Plant, Zaporizhvohnetryv, Ukrgrafit and Zaporizhtransformator. The concentration of phenolic compounds was found to be significantly higher under the technogenic conditions compared to the relatively "clean" area. Their highest concentration was found in the leaves of woody plants growing in the forest belt near the Zaporizhcoke plant. For the level of accumulation in the organs of assimilation of trees, and thereby for the degree of air pollution by the phenolic compounds, enterprises can be ranked as follows: Zaporizhcoke > Zaporizhstal ≥ Zaporizhzhya Ferroalloy Plant > Zaporizhvohnetryv > Ukrgrafit > Zaporizhzhya Aluminium Plant > Zaporizhzhya Titanium & Magnesium Combine > Zaporizhzhya Abrasive Plant > Zaporizhtransformator. Depending on the level of accumulation of phenolic compounds in the leaves, the plants have been divided into three groups. The largest amount of the pollutant, compared to the other species of woody plants, is being accumulated by the leaves of the following species: Ailanthus altissima, Betula pendula, Juglans regia, Populus alba, Populus nigra, Populus piramidalis, Populus simonii, Elaeagnus angustifolia, and the least amount – by Morus alba, Robinia pseudoacacia, Tilia cordata, Ulmus carpinifolia, Armeniaca vulgaris, Fraxinus lanceolata. The following species occupy the intermediate position between the two groups: Acer negundo, Acer platanoides, Aesculus hippocastanum, Catalpa bignonioides, Salix alba, Ulmus laevis. The tree species that can be characterized by their capacity to accumulate the highest concentration of water-soluble phenolic compounds may be recommended for the purpose of purification of atmospheric air. The following plant species, which turned to be the most sensitive indicators of air pollution, have been listed in a descending order according to the value of the coefficient of relative accumulation of phenolic compounds. Such species include Betula pendula, Catalpa bignonioides, Elaeagnus angustifolia, Ailanthus altissima, Populus simonii, Acer negundo, Ulmus laevis and Fraxinus lanceolata.